ORAL LANGUAGE USE AND LANGUAGE LEARNING OPPORTUNITIES IN EFL CLASSROOM: SHAMBU SECONDARY SCHOOLS GRADE 10 IN FOCUS - Gabisa, Dereje; Gutema, Hailu (Universitas Islam Sumatera Utara (UISU), 2024)
In this study, oral language use was examined in the context of interpersonal communication in order to identify the potential for EFL acquisition. The researchers have chosen a qualitative research approach to help them accomplish the aforementioned goal. In Shambu Town, Oromia, Ethiopia, secondary schools were systematically observed and 45-minute chunks from four EFL teaching courses were videotaped for the study. It is discovered that the teacher fosters language acquisition by overseeing student efforts and emergent knowledge gap fillers by using meticulous transcriptions of such activities and the micro analytic lens of conversation analysis. The efficient use of resources, including corrections, prompt repairs, and thorough explanation, serves as a proof of this. The study offered suggestions for how to enhance L2 acquisition by mixing up language usages in the classroom. The findings have significance for research on interactions in EFL classes, directed language learning, and studies on oral language use in language learning.